2007
DOI: 10.4319/lo.2007.52.3.1139
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced coral growth between organic tissue and carbonate skeleton caused by nutrient enrichment

Abstract: Effects of moderate nutrient enrichment (NO { 3 : ,5 mmol L 21 , PO 3{ 4 : ,0.3 mmol L 21 ) on two carbon (C) fixation rates (photosynthesis and calcification) of the zooxanthellate coral Acropora pulchra were investigated under laboratory conditions. The coral branches were incubated in the nutrient condition for three different periods (0, 5, 10 d) to observe changes in tissue biomass and zooxanthellate chlorophyll a (Chl a) concentration. Next, the incubated corals were simultaneously transferred to nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 41 publications
(61 reference statements)
10
56
2
Order By: Relevance
“…In a few experiments involving a moderate increase in nitrogen and/or phosphorus levels, an enhancement of coral metabolism was instead observed (Meyer and Schultz, 1985;Tanaka et al, 2007;Godinot et al, 2011). Our results with non-stressed nubbins of T. reniformis (C-26 and N-26 samples) add to the growing body of evidence that a slight increase in nutrient concentration in seawater does not necessarily impact coral health.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In a few experiments involving a moderate increase in nitrogen and/or phosphorus levels, an enhancement of coral metabolism was instead observed (Meyer and Schultz, 1985;Tanaka et al, 2007;Godinot et al, 2011). Our results with non-stressed nubbins of T. reniformis (C-26 and N-26 samples) add to the growing body of evidence that a slight increase in nutrient concentration in seawater does not necessarily impact coral health.…”
Section: Discussionsupporting
confidence: 51%
“…Nitrogen-enriched corals, however, presented a decrease in organic carbon release, likely due, in the present experiment, to a higher utilization of photosynthetically acquired carbon, in combination with nitrogen, to form molecules of interest such as proteins. Three other studies have investigated the release of organic carbon by scleractinian corals in the presence of elevated nutrient concentrations (Tanaka et al, 2007;Naumann et al, 2010;Bednarz et al, 2012), and have also observed a reduced release or an increased uptake of organic carbon. In Bednarz et al (Bednarz et al, 2012), it was hypothesized that the enhanced uptake of dissolved organic carbon by the soft coral Xenia under nitrogen enrichment was due to a need for additional carbon compounds following the decrease in photosynthetic rates and carbon translocation of the symbionts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marubini and Davies, 1996;Reynaud et al, 2003;Houlbreque et al, 2004;Tanaka et al, 2007). Such results point to the importance of multiple factors in determining rates of coral calcification.…”
Section: Discussionmentioning
confidence: 81%
“…Under low ambient inorganic nutrient concentrations, zooxanthellae metabolism and growth are limited with respect to nitrogen, and carbon is photosynthetically fixed in excess. This surplus in carbon is translocated to the host together with small amounts of nitrogen Stimson and Kinzie, 1991;Tanaka et al, 2006). At elevated inorganic nitrogen levels in ambient seawater, zooxanthellae are enabled to retain more carbon for their own metabolism and growth, and consequently less of it is being translocated to their host (Dubinsky and Jokiel, 1994).…”
Section: Enrichment Effects On Doc Fluxesmentioning
confidence: 99%